2022
DOI: 10.12911/22998993/145478
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Soil Pollution Levels in Al-Qadisiyah Governorate, Iraq Using Contamination Index and GIS

Abstract: The precise determination of trace element concentrations in the soil of the Al-Qadisiyah Governorate is part of the Iraqi sedimentary plain is required to eliminate high levels of harmful elements in polluted soils. The soil samples were collected from 28 representative profiles in Al-Shamiyah city. The soil profiles were defined using virtual characterization. In this study, I-geo was used to analyze soil pollution. The goals and destinations of the I-geo readings Contamination of Cd, Ni, Pb, and Zn in vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Likewise, Zhuang et al (2016) found concentrations of Cd and Pb are associated with anthropogenic activities in agricultural soil in Gongzhuling, Northeast of China. Other studies were also explored in the city of Qadisiyah/Iraq and, specifically in the city of Al-Shamiyah, to investigate spatial levels of heavy metals by using geographic information systems and pollution indices in agricultural soil (Al-Khuzaie and Abdul Maulud, 2022). In a study also in Al-Diwaniyah Governorate by AlHamzawi and AlGharabi (2019), different concentrations were found in industrial, residential and agricultural soils in various cities in the governorate.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Zhuang et al (2016) found concentrations of Cd and Pb are associated with anthropogenic activities in agricultural soil in Gongzhuling, Northeast of China. Other studies were also explored in the city of Qadisiyah/Iraq and, specifically in the city of Al-Shamiyah, to investigate spatial levels of heavy metals by using geographic information systems and pollution indices in agricultural soil (Al-Khuzaie and Abdul Maulud, 2022). In a study also in Al-Diwaniyah Governorate by AlHamzawi and AlGharabi (2019), different concentrations were found in industrial, residential and agricultural soils in various cities in the governorate.…”
Section: Introductionmentioning
confidence: 99%